Green synthesis of silver nanoparticles using Capsicum frutescence and its intensified activity against E. coli; Resource-Efficient Technologies; Vol. 3, iss. 3 - Thangaraj Shankar; Perumal Karthiga; Kalaiyar Swarnalatha; Kalaiyar Rajkumar (2017, 2017)
Title screen